Disorders of Sex Development: Lessons to be Learned from Studies of Spina Bifida and Craniofacial Conditions - Holmbeck, G. N.; Aspinall, C. L. (Hormone and Metabolic Research, 2015)
The purpose of this review is to discuss research methods and clinical management strategies employed with other conditions (i. e., spina bifida and craniofacial conditions) and how these methods and strategies could be applied to youth with disorders of sex development (DSD). The review focuses specifically on the potential overlap between DSD and these other conditions across the following 3 areas: (1) developmentally-oriented theories that underlie the research base for chronic physical conditions; (2) research designs and methodological features that have proved fruitful in these areas; and (3) the potential applicability to DSD of clinical management practices for youth with craniofacial conditions.
Keywords: DSD; spina bifida; craniofacial conditions; research design; clinical management